Development of the “Rehcardicare” Application for Post-Coronary Rehabilitation Artery Bypass Graft for Improving Cardiac Endurance Through Resistance and Flexibility Training - Rinawati Rinawati; Lidia Silaban (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Coronary heart disease (CHD) is a heart abnormality caused by narrowing or obstruction of the coronary arteries supplying blood to the heart. Objective: This study aimed to investigate the development of the "Rehcardicare" application after CABG to improve patients' cardiac endurance using resistance and flexibility. It also measured the effectiveness of the "Rehcardicare" application in improving cardiac endurance after CABG. It also identifies patient attitudes toward the "Rehcardicare" application. Methods: The design used a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data were collected on patient characteristics, patient understanding of heart conditions, the CABG procedure, and the importance of rehabilitation. Data were collected on initial cardiac functional capacity, digital records of "Rehcardicare" application usage, improvements in cardiovascular functional capacity, and patient attitudes toward "Rehcardicare" application-based rehabilitation. Implementation of post-CABG patient rehabilitation using the "Rehcardicare" Rehabilitation application through resistance and flexibility training and the effectiveness of the "Rehcardicare" rehabilitation application in increasing cardiac endurance and data were analyzed using a t-test with a 95% confidence interval. Results: The age of respondents was more with 8 people aged 51-60 years (44.4%) with a gender that was more with men as many as 15 people (83.3%), the occupation of respondents was more with self-employed as many as 12 people (66.7%), patients were able to identify problems that arose during rehabilitation, there was an increase in the distance traveled by the 6 Minute Walk Test (6MWT) compared to the baseline results before rehabilitation by 100%. The design of the "Rehcardicare" rehabilitation application was effective in increasing cardiac endurance in post-CABG patients with a p-value = 0.000 < α = 0.05 Conclusion: The design of the “Rehcardicare” rehabilitation application was successfully designed by integrating resistance and flexibility exercises, assessment indicators, and digital monitoring that are appropriate to the needs of post-CABG patients, the application has been proven to be effective in increasing cardiac endurance, which is indicated by an increase in the results of the Six Minute Walk Test (6MWT) and improvements in the functional capacity of patients, the implementation of rehabilitation through the application patients to do exercises safely, structured, and consistently, while making it easier for medical personnel to monitor patient progress and post-CABG patients show a positive attitude towards application-based rehabilitation, by assessing the application as easy to use, useful, and increasing motivation and adherence to the program and the “Rehcardicare” application has the potential to be an effective alternative to cardiac tele-rehabilitation, especially to support patients who have difficulty following face-to-face rehabilitation in hospitals.